Analysis of Surface Water Potential for Domestic Water Use in Gunungkidul Ecoregion - Husnul Khotimah Setiacahyandari; Alfina Ayu Rachmawati; Alvin Anindita Katon Sumunar; Atina Tsabita Khairunnisa; Lupiya Cintantya Anindita; Nabila Laili Udzkhiyati; Slamet Suprayogi (Jurnal Pendidikan Geografi Gea, 2022)
Gunungkidul is characterized by its high rainfall intensity, high population, and various ecoregions with predominated by karst, all of which can affect the availability of surface water. Therefore, this study aimed to analyze the surface water potential for domestic use in the Gunungkidul ecoregion. This analysis is carried out by calculating water use index through a comparison of domestic water demand and surface water availability in Gunungkidul. The results show that the availability of surface water in Gunungkidul was not able to fulfill the population's domestic water needs throughout the year. It is proved by the fact that some ecoregions in July and all ecoregions in August have a surface water use index of more than 0,2 and are classified as poor and very poor classes. Ecoregion with the highest surplus of surface water is Gunung Sewu Karst Hills which is reflected by the lowest surface water use index. In contrast, Wonosari Karst Basin has the lowest surface water potential shown by the high value of its surface water use index. Based on these results, it is known that the main factors that affect the water use index are the area of each ecoregion, population, rainfall, geological and geomorphological conditions.